2009
DOI: 10.1007/s10725-009-9416-6
|View full text |Cite
|
Sign up to set email alerts
|

The alternative pathway in cucumber seedlings under low temperature stress was enhanced by salicylic acid

Abstract: The alternative pathway is a cyanide-resistant and non-phosphorylatory electron transport pathway in mitochondria of higher plants. Alternative oxidase (AOX) is the terminal oxidase of this pathway. Our present study investigated the effect of exogenous salicylic acid (SA) on alternative pathway in cucumber (Cucumis sativus L.) seedlings under low temperature stress. Results showed that during the process of low temperature stress, the alternative pathway capacity was enhanced as AOX expression increased in SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 54 publications
1
23
0
2
Order By: Relevance
“…For example, exogenous SA treatment could improve chilling tolerance in maize (Janda et al 1999;Horvath et al 2002), tomato (Ding et al 2002), banana (Kang et al 2003), winter wheat (Tasgin et al 2006;Esim and Atici 2015), guayule (Sundar et al 2004), red globe grape (Li et al 2005), Brassica juncea (Setia et al 2006), radish (Biao, 2006), cucumber (Xia et al 2007;Lei et al 2010), grass (Wang et al 2009a) and barley (Mutlu et al 2013a(Mutlu et al , 2013b. Recently, some researchers carried out on winter wheat (Tasgin et al 2006) and watermelon (Yang et al 2008) demonstrated that exogenous SA treatment could be involved in cold tolerance by regulating the activities of antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exogenous SA treatment could improve chilling tolerance in maize (Janda et al 1999;Horvath et al 2002), tomato (Ding et al 2002), banana (Kang et al 2003), winter wheat (Tasgin et al 2006;Esim and Atici 2015), guayule (Sundar et al 2004), red globe grape (Li et al 2005), Brassica juncea (Setia et al 2006), radish (Biao, 2006), cucumber (Xia et al 2007;Lei et al 2010), grass (Wang et al 2009a) and barley (Mutlu et al 2013a(Mutlu et al , 2013b. Recently, some researchers carried out on winter wheat (Tasgin et al 2006) and watermelon (Yang et al 2008) demonstrated that exogenous SA treatment could be involved in cold tolerance by regulating the activities of antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment of hybrid corn seeds with exogenous SA considerably improved seedling emergence, root and shoot length, and seedling fresh and dry weight, all compared with the controls, both at optimal temperatures and under cold stress temperatures (Farooq et al 2008). Finally, exogenously applied SA alleviated the cold stress effect on growth of cucumber seedlings (Lei et al 2010). Thus, there is a plethora of examples where a pre-treatment with exogenous SA has reduced the negative effects of cold stress on plant growth and metabolism.…”
Section: Temperature and Endogenous Salicylic Acid Levelsmentioning
confidence: 91%
“…For light and dark treatments, soybean plants were divided into two groups and grown under continuous light or in complete darkness for 12 h, respectively, in growth chambers. Different organs, including roots, stems, leaves, flowers and pods were collected to extract total RNA as described by Lei et al (2010).…”
Section: Methodsmentioning
confidence: 99%